Water as a determinant of the distribution of trees at the boundary of the Mediterranean zone. - Pigott, C D; Pigott, S (Journal of Ecology, 1993)
Investigates the water relations of two species, Quercus ilex and Tilia cordata (T. cordata) in southern France. Effect of drought on the growth in height and stem diameter of T. cordata; Importance of water supply in controlling both the small and large scale pattern of distribution of T. cordata.
Keywords: Quercus ilex; Tilia cordata; water potential